Stem cell therapies in the clinic - Shrinivas Acharya; Suyog Shaha; Michael Griffith Bibbey; Malini Mukherji; Zongmin Zhao; Samir Mitragotri (Bioengineering & Translational Medicine)
Abstract Stem cell therapies have emerged as a transformative approach in modern medicine, with the potential to address and possibly cure a broad spectrum of diseases. These therapies utilize living stem cells that can perform complex biological functions not replicable by traditional drugs. Stem cell therapies have an expanding therapeutic landscape, with several products already approved and numerous clinical trials underway. Among the various stem cell types, hematopoietic stem cells (HSCs) and mesenchymal stem cells (MSCs) are most widely studied. In this review, we provide a detailed analysis of the current clinical landscape of stem cell therapies. We review 27 stem cell products that have received regulatory approvals and discuss 800 ongoing clinical trials, with a focus on HSCs and MSCs. We also discuss the critical challenges to be addressed to facilitate the clinical translation of stem cell therapies.